Identification of miRNAs-mediated seed and stone-hardening regulatory networks and their signal pathway of GA-induced seedless berries in grapevine (V. vinifera L.) - Peipei Wang; Xuxian Xuan; Ziwen Su; Wenran Wang; Mostafa Abdelrahman; Songtao Jiu; Xiaowen Zhang; Zhongjie Liu; Xicheng Wang; Chen Wang; Jinggui Fang (BMC Plant Biology, 2021)
Abstract Background Stone-hardening stage is crucial to the development of grape seed and berry quality. A significant body of evidence supports the important roles of MicroRNAs in grape-berry development, but their specific molecular functions during grape stone-hardening stage remain unclear. Results Here, a total of 161 conserved and 85 species-specific miRNAs/miRNAs* (precursor) were identified in grape berries at stone-hardening stage using Solexa sequencing. Amongst them, 30 VvmiRNAs were stone-hardening stage-specific, whereas 52 exhibited differential expression profiles during berry development, potentially participating in the modulation of berry development as verified by their expression patterns. GO and KEGG pathway analysis showed that 13 VvmiRNAs might be involved in the regulation of embryo development, another 11 in lignin and cellulose biosynthesis, and also 28 in the modulation of hormone signaling, sugar, and proline metabolism. Furthermore, the target genes for 4 novel VvmiRNAs related to berry development were validated using RNA Ligase-Mediated (RLM)-RACE and Poly(A) Polymerase-Mediated (PPM)-RACE methods, and their cleavage mainly occurred at the 9th–11th sites from the 5′ ends of miRNAs at their binding regions. In view of the regulatory roles of GA in seed embryo development and stone-hardening in grape, we investigated the expression modes of VvmiRNAs and their target genes during GA-induced grape seedless-berry development, and we validated that GA induced the expression of VvmiR31-3p and VvmiR8-5p to negatively regulate the expression levels of CAFFEOYL COENZYME A-3-O-METHYLTRANSFERASE (VvCCoAOMT), and DDB1-CUL4 ASSOCIATED FACTOR1 (VvDCAF1). The series of changes might repress grape stone hardening and embryo development, which might be a potential key molecular mechanism in GA-induced grape seedless-berry development. Finally, a schematic model of miRNA-mediated grape seed and stone-hardening development was proposed. Conclusion This work identified 30 stone-hardening stage-specific VvmiRNAs and 52 significant differential expression ones, and preliminary interpreted the potential molecular mechanism of GA-induced grape parthenocarpy. GA negatively manipulate the expression of VvCCoAOMT and VvDCAF1 by up-regulation the expression of VvmiR31-3p and VvmiR8-5p, thereby repressing seed stone and embryo development to produce grape seedless berries.